INSTITUTIONAL REPOSITORY AND PUBLICATION OF UNIVERSITY RESEARCH RESULTS: A CASE OF A SWEDISH REGIONAL UNIVERSITY - MACEVIČIŪTĖ, ELENA; WILSON, THOMAS D. (Knygotyra, 2013)
The article presents a study that is based on the statistical analysis of the data from the university institutional repository, on the analysis of the university documents regulating the publishing of research results, interviews with the policy makers in the university and with active researchers, as well as the analysis of the survey data collected from the research staff. The problem that the study holds in focus was introduction and perception of open access publishing among researchers. This problem was related to the general publishing policy in Swedish universities and the policies of research funding on the national and institutional levels. The actual study was carried out as a case study of a medium regional university in Sweden. The university holds research rights in several research areas and supports open access through institutional publishing policy. The study included several methods that helped providing answers to the following questions: What are the provisions of the University management that lead to the formulation of the policy requirements for publishing research results?What is the impact of publishing policies on the actual publication of research results?How do the researchers perceive the publishing policy of the University, the requirements and open access?What do the researchers know about the functions of the institutional repository at the University and the repository data quality problems?The results of the study show that the publishing policy of the university seeks to increase the visibility of the university in scholarly communication, create open access to the research results of the university and improve the quality of published documents. It also emphasizes the responsibility of researchers for the quality of publications and the data that represents them. The knowledge of the university researchers about the publication processes and the potential of open access, about the consequences of the transfer of copyright to publishers or other processes related to modern scholarly communication is rather limited. Though their attitudes towards open access are positive, the responsibility of a researcher for implementation of open access and the quality of the data or documents accessible through it is not recognized. Successful implementation of the publishing policies in the university require continued information literacy education for researchers and increased consultations about publishing changes. This could become a natural extension of library functions related to both its work with institutional repository and information literacy.
Keywords: ...